2014
DOI: 10.1097/olq.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Provider Characteristics Associated With Guideline-Nonadherent Gonorrhea Treatment, Massachusetts, 2010

Abstract: Emerging antibiotic resistance may be slowed through effective implementation of treatment guidelines. Our case-control study showed that providers who treated gonorrhea differently from guidelines in Massachusetts accounted for approximately 4% of cases and were associated with private practice/health maintenance organization settings and lower-incidence locations. Patient β-lactam allergy was also significantly associated with guideline nonadherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
3
2
0
Order By: Relevance
“…However, in practice, many factors might influence provider’s adherence to the recommended regimen, including the availability of injectable medications at the time of treatment and patient-reported allergies. In the current analysis, patients diagnosed with gonorrhea in STD and family planning/reproductive health clinics were more likely to be treated with the recommended regimen than were patients diagnosed in other provider settings, similar to observations from earlier studies ( 7 , 8 ). Across all provider settings, MSM were more likely to be treated with the recommended regimen, and MSM were more likely than non-MSM to receive a diagnosis in STD clinics.…”
Section: Discussionsupporting
confidence: 85%
“…However, in practice, many factors might influence provider’s adherence to the recommended regimen, including the availability of injectable medications at the time of treatment and patient-reported allergies. In the current analysis, patients diagnosed with gonorrhea in STD and family planning/reproductive health clinics were more likely to be treated with the recommended regimen than were patients diagnosed in other provider settings, similar to observations from earlier studies ( 7 , 8 ). Across all provider settings, MSM were more likely to be treated with the recommended regimen, and MSM were more likely than non-MSM to receive a diagnosis in STD clinics.…”
Section: Discussionsupporting
confidence: 85%
“…We found that, among patients presenting with STI symptoms and/or known contact (i.e., those who may have merited presumptive or empiric therapy), a longer TTT was significantly more likely to occur among females than males, even after controlling for other factors. Presumptive or empiric treatment was also less likely when the provider practice had less experience diagnosing gonorrhea, in line with previous study demonstrating reduced guideline adherence in lower-incidence locations 29 . The gender differences that we found have been observed in prior studies 15 .…”
Section: Discussionsupporting
confidence: 91%
“…Presumptive or empiric treatment was also less likely when the provider practice had less experience diagnosing gonorrhea, in line with previous study demonstrating reduced guideline adherence in lower-incidence locations. 29 The gender differences that we found have been observed in prior studies. 15 As previously mentioned, symptoms of STIs in women can be non-specific, making it harder for clinicians to treat empirically upon presentation.…”
Section: Discussionsupporting
confidence: 68%
“…Lechtenberg et al audited the treatment given to a randomly selected sample of patients with gonorrhoea in California between 2009 and 2011 . Swails et al audited the treatment of all patients with gonorrhoea in Massachusetts during 2010 . However, we are not aware of any other large studies that audited the level of guideline compliance across the wide range of services that care for patients with gonorrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…14 Swails et al audited the treatment of all patients with gonorrhoea in Massachusetts during 2010. 15 However, we are not aware of any other large studies that audited the level of guideline compliance across the wide range of services that care for patients with gonorrhoea. A large US study documented a dramatic decline between 2006 and 2008 in the proportion of patients with gonorrhoea who were treated with a fluoroquinolone but did not determine the proportion of patients whose treatment was guideline compliant.…”
Section: Discussionmentioning
confidence: 99%